Axial spondyloarthritis and COVID-19: course, interactions, outcomes, and the role of vaccination - Sh. F. Erdes; B. S. Belov (Современная ревматология)
The review analyzes data on the course and outcomes of axial spondyloarthritis (axSpA) accumulated over the previous 2.5 years of the COVID-19 pandemic. The issues of clinical and immunological efficacy of vaccination against COVID-19 in this disease are considered. It was noted that the presence of axSpA, as well as treatment with tumor necrosis factor-á inhibitors and non-steroidal anti-inflammatory drugs, did not significantly increase the risk of COVID-19 infection and did not worsen its outcomes, apart from an increase in the incidence of venous thromboembolism. At the same time, it is assumed that anticytokine therapy for SpA may protect against severe COVID-19 course.The data presented suggest that the benefits of vaccination in SpA far outweigh the potential harms associated with the development of adverse events. It has been shown that in patients with SpA, vaccination does not affect the activity of the inflammatory process, and biologic disease modifying antirheumatic drugs have almost no significant effect on the post-vaccination response.